2020
DOI: 10.1590/1982-0216/20202210120
|View full text |Cite
|
Sign up to set email alerts
|

Tongue position for lingual frenulum assessment

Abstract: Purpose: to compare the movements of elevation and protrusion of the tongue in order to determine which position provides better lingual frenulum assessment. Methods: a database of 92 audiovisual recordings of subjects over six-years of age diagnosed with ankyloglossia was used to verify the shape of the tip of the tongue during tongue elevation and protrusion. The Chi-Square Test for Proportion was applied to verify possible differences between the postures of elevation and protrusion. The significance level … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 23 publications
1
4
1
Order By: Relevance
“…In nursing newborns, there was also a weak association between tongue and lips posture at rest (closed, parted, or open lips). This is in contrast to a study 23 that showed no correlations between these characteristics. The analysis of tongue and lip position, in combination with the other evaluation criteria, is thought to aid in identifying any abnormalities in the lingual frenulum.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In nursing newborns, there was also a weak association between tongue and lips posture at rest (closed, parted, or open lips). This is in contrast to a study 23 that showed no correlations between these characteristics. The analysis of tongue and lip position, in combination with the other evaluation criteria, is thought to aid in identifying any abnormalities in the lingual frenulum.…”
Section: Discussioncontrasting
confidence: 99%
“…The intraoral exam revealed only a difference in tongue scores in nursing infants, with males having lower findings, which corresponds to a study 23 that identified a higher incidence of frenulum abnormalities in boys. Another study 4 found that similar changes are common in newborn males.…”
Section: Discussionsupporting
confidence: 86%
“…The tongue's range of motion is examined: lifting, forward, and lateral extension. An important part of this assessment is to observe the movement of the mandible during tongue movements, as the mandible should then be stable [4,5,[20][21][22]. According to Zaghi, an indicator of the range of tongue movement is the measurement of TRMR -tongue range of motion ratio [5].…”
Section: Assessment Of the Tongue's Range Of Motionmentioning
confidence: 99%
“…Functional assessment [4,5,7,12,[18][19][20][21]23] -opinion of speech therapy: • normal tongue mobility -0 points; • slight limitation of tongue mobility -1 point:…”
Section: Functional Assessmentmentioning
confidence: 99%
“…One of the biggest limiting factors for clinical research on the topic of ‘functional ankyloglossia’ is the paucity of objective measurements to define the presence or absence of the condition. Most definitions of the condition are based on structural characterisations of the lingual frenulum 15,17‐19 or subjective descriptions of mobility, 20‐24 as there are limited objective tools to actually quantify functional variations in tongue mobility on a continuous numeric scale 25…”
Section: Introductionmentioning
confidence: 99%